358. Sociodemographic and clinical features of children and adolescents with SARS-CoV-2 infection in Nashville, Tennessee. (31st December 2020) - Howard, Leigh; Garguilo, Kathryn; Gillon, Jessica; Webber, Steven; Halasa, Natasha B; Banerjee, Ritu; Banerjee, Ritu
Abstract: Background: Little is known regarding the full spectrum of illness among children with SARS-CoV-2 infection across integrated healthcare settings, as many published pediatric cohorts focus on hospitalized patients with SARS-CoV-2 infection. Methods: Active surveillance was performed for SARS-CoV-2 detections among symptomatic and asymptomatic children and adolescents ≤18 years of age in a quaternary care academic hospital laboratory in the Southeastern U.S. For symptomatic patients with a positive respiratory specimen for SARS-CoV-2 by polymerase chain reaction (PCR), and for neonates born to SARS-CoV-2-positive mothers, we performed phone follow-up and medical record review at days 2, 7, and 30 after diagnosis. Testing was initiated 3/12/20 for symptomatic patients and 5/4/20 for screening asymptomatic patients. Results: By 6/14/20, SARS-CoV-2 tests were positive in 193/5306 (3.6%) specimens from unique patients ≤18 (Table 1 ), compared to 2653/36503 (7.2%) specimens in patients >18 years. Specimens from 181/2638 (6.8%) symptomatic and 12/2768 (0.4%) asymptomatic children were positive. Nine infants born to SARS-CoV-2 infected mothers had negative PCR tests at birth; 1 infant subsequently acquired SARS-CoV-2 infection at 5 weeks of age. Sociodemographic and clinical data for 181 SARS-CoV-2-positive symptomatic children are displayed in Table 2 and Figure 1. The most common symptoms were cough (59%), fever (50%), and rhinorrhea (39%). Nine/181 symptomatic patients (5%) were hospitalized, primarily for respiratory symptoms. Symptom resolution occurred by follow-up day 2 in 82/178 (46%) and day 7 in 128/164 (78%) patients with complete assessments to date. 131/181 (72%) of children had known SARS-CoV-2 positive contacts. We observed no cases of multisystem inflammatory syndrome in children. Conclusion: In our community, pediatric SARS-CoV-2 prevalence was low, but was much higher among symptomatic than asymptomatic children. Symptoms were mild, and the duration of symptoms brief, in the majority of these patients captured within an integrated ambulatory and hospital-based healthcare system, capturing the full spectrum of the disease profile in this age group. Disclosures: Natasha B. Halasa, MD, MPH, Genentech (Other Financial or Material Support, I receive an honorarium for lectures - it's a education grant, supported by genetech)Karius (Consultant)Moderna (Consultant)Quidel (Grant/Research Support, Research Grant or Support)Sanofi (Grant/Research Support, Research Grant or Support)